2011
DOI: 10.1111/j.1365-2702.2011.03708.x
|View full text |Cite
|
Sign up to set email alerts
|

Premenstrual dysphoric disorder: prevalence and effects on nursing students’ academic performance and clinical training in Kuwait

Abstract: Nursing students' absenteeism rate at clinical training is a predictor of their work absence pattern after qualification. Absenteeism due to premenstrual dysphoric disorder, a cyclic monthly disorder will be of monthly occurrences if sufferers do not sought medical treatment. Registered nurses absenteeism will not only result in shortage of trained nursing personnel, but also lowered standard of client care. It also has cost implications as temporary substitute staff may have to be employed during their period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 16 publications
2
19
3
Order By: Relevance
“…Unlike previous studies [32, 35, 4244], this study did not show a significant association between PMDD and history of depression, history of any psychiatric morbidity other than depression, history of traumatic event, sleeping hour, history of physical illness, increased educational status, physical exercise, marital status, age at menarche, and maternal history of PMS. This inconsistency may be due to difference in socioeconomic status and health seeking behavior of students.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Unlike previous studies [32, 35, 4244], this study did not show a significant association between PMDD and history of depression, history of any psychiatric morbidity other than depression, history of traumatic event, sleeping hour, history of physical illness, increased educational status, physical exercise, marital status, age at menarche, and maternal history of PMS. This inconsistency may be due to difference in socioeconomic status and health seeking behavior of students.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, the prevalence of PMDD was 13.8%. This finding was twice the prevalence rate of PMDD in Kuwait students [32], but on the other hand, it was lower than the Pakistani study report [33]. This discrepancy might be due to the difference in sample size, study population, and use of PMDD assessment tool.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…It is reported that premenstrual and menstrual symptoms affect the physical, mental, and social lives of young women . Studies conducted with university students have shown that the students’ absence from lectures negatively affects school success, quality of life, social activities, and family relations . In some studies, women with PMS have found to have somatic complaints because of psychological problems and high levels of alexithymia .…”
Section: Introductionmentioning
confidence: 99%
“…A review of literature for studies investigating relationship between alexithymia and premenstrual and menstrual symptoms in women of different age found only limited number of studies, and no studies conducted with nursing students. These students will be the future of health care professional and it is important to examine premenstrual and menstrual symptoms and alexithymia associated with it . Therefore, this study was conducted to determine the relationship of premenstrual and menstrual symptoms to alexithymia among nursing students.…”
Section: Introductionmentioning
confidence: 99%